Case report: imaging and treatment of ophthalmic manifestations in oculodentodigital dysplasia. Issue 1 (December 2016) - Mosaed, Sameh; Jacobsen, Bradley; Lin, Ken
Abstract Background Diagnostic and surgical management of severe chronic angle- closure glaucoma secondary to ciliary body cysts can be difficult to manage in a patient with oculodentodigital dysplasia. Case presentation A 6-year old girl with oculodentodigital dysplasia, with progressive chronic angle- closure glaucoma secondary to ciliary body cysts presented to our clinic. The initial examination revealed counting fingers vision in the left eye. Intraocular pressure (IOP), as assessed by tonopen, was 31 mm Hg. Ultrasound biomicroscopy revealed ciliary body cysts in the left eye, and gonioscopy confirmed chronic angle closure. A tube shunt was placed to control the elevated IOP. A year after her tube shunt placement in the left eye, ultrasound biomiscropy was performed on her right eye and showed no ciliary body cysts. Gonioscopy in the right eye revealed an open angle to the ciliary body band. Subsequent serial gonioscopy every 3 months showed gradual narrowing of the right eye angle and finally three-and-a-half years after tube placement of the left eye, her right eye IOP became uncontrolled with medications alone and a tube shunt was similarly placed in the right eye. Intraoperative ultrasound biomicroscopy performed at the time of the right eye tube shunt revealed extensive ciliary body cysts in the right eye. Her IOP in both eyes have been well controlled since the placement of tube shunts. Conclusions This is one of the first reported cases of severe chronic angle- closure glaucoma secondary to ciliary body cysts in a patient with oculodentodigital dysplasia. We believe that early screening for ciliary body cysts is important in patients with oculodentodigital dysplasia.